F(x) = 3x + 1
let f(x) = y
y = 3x + 1
y - 1 = 3x
3x = y - 1
x = (y - 1)/3
From y = f(x), x = f⁻¹(y)
<span>x = (y - 1)/3
</span>
f⁻¹(y) = (y - 1)/3
f⁻¹(7) = <span>(7 - 1)/3 = 6/3 = 2
</span>f⁻¹(7)<span> = 2</span>
Answer:
4x^2 -12x +9 ft^2
Step-by-step explanation:
The area of a square is
A = s^2 where s is the side length
A = (2x-3) ^2
A = (2x-3) (2x-3)
FOIL
first 2x*2x =4x^2
outer 2x (-3) = -6x
inner -3*2x = -6x
last -3*-3 = 9
Add them together
4x^2 -6x-6x +9
Combine like terms
4x^2 -12x +9
The area is 4x^2 -12x +9 ft^2
About less than 3 inches :)
Y= 40 explanation don’t want to just trust me it’s 40
The correct answer is 0.78. Hope this helps.